Assembly of Short Oligoribonucleotides from Commercially Available Building Blocks on a Tetrapodal Soluble Support - Gimenez Molina, Alejandro; M. Jabgunde, Amit; Virta, Pasi; Lonnberg, Harri (Current Organic Synthesis, 2015)
A workable method for the preparation of short oligoribonucleotides from commercially available 5´-O-(4,4´- dimethoxytrityl)-2´-O-(tert-butyldimethylsilyl)ribonucleoside 3´-(2-cyanoethyl-N,N-diisopropylphosphoramidite) building blocks on a soluble tetrakis-O-[4-(1,2,3-triazol-1-yl)methylphenyl]pentaerythritol support has been developed. The 3´-terminal nucleoside was attached as a 3´-O-(4-pentynoyl) derivative to the support by Cu(I) catalyzed click reaction. The coupling cycle consisted of 4,5-dicyanoimidazole promoted coupling in MeCN with 1.5 equiv. of the monomeric building block, conventional iodine oxidation and precipitation from water followed by flash chromatographic purification. Treatment with triethylamine, followed by ammonolysis and desilylation with Et3N(HF)3 afforded the oligoribonucleotide. As a proof of concept, a pentamer 3´-UUGCA-5´ was prepared in 46% overall yield.
Keywords: soluble support